2005
DOI: 10.1080/00049530412331283417
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in age and self-efficacy in the unemployed

Abstract: The purpose of the present study was to investigate the role of age in influencing the relationships among general self‐efficacy, proactive attitude, and proactive coping in unemployed people. The sample consisted of 55 male and 49 female unemployed Australians participating in Job Search Training courses. They completed the General Self‐Efficacy (GSE) Scale, the Proactive Attitude (PA) Scale, and the Proactive Coping (PC) Scale. The GSE, PA, and PC scores were found to be correlated, and a moderating effect f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Efficacious folk believe that they can change situations and behaviours to produce more positive outcomes for themselves. These findings raise the question of whether negative perceptions and powerlessness can be converted into positive attitudes and self-efficacy in the young (Albion et al, 2002).…”
Section: In Search Of An Answermentioning
confidence: 95%
See 3 more Smart Citations
“…Efficacious folk believe that they can change situations and behaviours to produce more positive outcomes for themselves. These findings raise the question of whether negative perceptions and powerlessness can be converted into positive attitudes and self-efficacy in the young (Albion et al, 2002).…”
Section: In Search Of An Answermentioning
confidence: 95%
“…Interestingly, Albion et al (2002) found a correlation between age and self-efficacy in the unemployed. Older participants tended to be more efficacious due to the positive reinforcement of their decision making over time, whereas the young did not enjoy such self-assurance to the same degree.…”
Section: In Search Of An Answermentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Albion, Fernie & Burton [2005] have shown that age positively moderated effects on proactive behaviours that include positive attitudes and coping styles. Factors indicating participants' experience (i.e., age and belt rank in a martial art) could therefore have an effect on SF.…”
Section: Martial Arts Studiesmentioning
confidence: 99%